Enhancing Police Integrity - Klockars, Carl B. author. aut Link
XXIV, 276 p.
Keywords: How can we enhance police integrity? The authors surveyed over 3000 police officers from 30 U.S. police departments on how they would respond to typical scenarios where integrity is challenged. They studied three police agencies which scored highly on the integrity scale: Charlotte-Mecklenburg, North Carolina; Charleston, South Carolina; and St. Petersburg, Florida. The authors conclude that enhancing police integrity goes well beyond culling out "bad apple" police officers. Police administrators should focus on four aspects: organizational rulemaking; detecting, investigating and disciplining rule violations; circumscribing the informal "code of silence" that prohibits police from reporting the misconduct of their colleagues; and understanding the influence of public expectations and agency history.